Computational insights into the corrosion inhibition potential of some pyridine derivatives: A DFT approach - Thakur, Abhinay; Kumar, Ashish (European Journal of Chemistry, 2023)
In the present investigation, the corrosion inhibition potency of five pyridine derivatives was computationally simulated and investigated by utilizing the Density Functional Theory (DFT) technique using a basis set of B3LYP/6-31++G (d,p). The predicted corrosion inhibition capacity was shown to improve in the order of 6-(trifluoromethyl) nicotinic acid > 4-(trifluoromethyl) nicotinic acid > N-methyl-4-chloropyridine-2-carboxamide > 2-chloro-6-trifluoromethylnicotinic acid > methyl 2-aminopyridine-4-carboxylate. Anticorrosion potentials were predicted using quantum chemical variables such as energy gap (∆E) i.e. HOMO-LUMO, ionization potential (I), electron affinity (A), proportion of electrons transmitted (∆N), hardness (η), softness (σ) and electronegativity (χ) of chemical species. It was often observed that the corrosion inhibiting rate improved with enhancement of EHOMO, σ, and reduced ELUMO, ∆E and η. Additionally, the electrostatic potential (ESP) mapping revealed that the heteroatoms, including the oxygen and nitrogen atoms, were the regions of anticipated electrophilic attack. This meant that atoms of oxygen and nitrogen could form bonds between the metallic substrate atoms and the investigated inhibitors. With the findings obtained, 4-methyl-2-aminopyridine-4-carboxylate showed the highest EHOMO (-0.23167 eV), softness (12.40694 eV-1) and the lowest ELUMO (-0.7047 eV), energy gap (0.1612 eV) and hardness (0.15107 eV), therefore revealed the excellent corrosion inhibiting attribution for several crucial metals and alloys, including aluminum, mild steel, stainless steel, zinc, brass, copper, etc.